2010
DOI: 10.1002/ppap.200900112
|View full text |Cite
|
Sign up to set email alerts
|

Micro‐/Nanoscale Structuring of Cell‐Culture Substrates with Fluorocarbon Plasmas

Abstract: We describe the tailoring of polymer surfaces with CF x composition and roughness/density of different micro-/nanometric relieves (ribbons, petals, domes, dots) tuned independently in low pressure plasma deposition and etching processes. Similarity of outer chemical composition grants the comparison of cell culture results to analyze the impact of topographical features on cellular behavior. Such surfaces are of interest for biomedical substrates since tuning their surface composition and morphology can drive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 56 publications
1
41
0
Order By: Relevance
“…Unlike conventional polymers, plasma polymers are characterized by rather irregular and random structures with much higher level of cross‐linking. In spite of the complexity of their chemical structure, plasma polymers are valuable materials as their properties may be tuned by operational conditions (e.g., precursor, working gas mixture, power, excitation frequency), which allowed production of thin films with tailorable chemical, physical, or bioadhesive/biorepulsive properties as it was proven by numerous studies …”
Section: Introductionmentioning
confidence: 99%
“…Unlike conventional polymers, plasma polymers are characterized by rather irregular and random structures with much higher level of cross‐linking. In spite of the complexity of their chemical structure, plasma polymers are valuable materials as their properties may be tuned by operational conditions (e.g., precursor, working gas mixture, power, excitation frequency), which allowed production of thin films with tailorable chemical, physical, or bioadhesive/biorepulsive properties as it was proven by numerous studies …”
Section: Introductionmentioning
confidence: 99%
“…These approaches go from low pressure plasma treatments to graft N‐ or O‐containing functionalities, using NH 3 , N 2 , O 2 , CO 2 as gas feed; to plasma depositions with gas precursors like alkyl amines, acrylic acid, allyl alcohol, ethylene/N 2 , allylamine/acrylic acid; to some first attempts with atmospheric pressure discharges . Plasma processes can modify the surface topography, creating micro‐/nano‐motifs, and improving their biocompatibility, e.g., with fluorocarbon monomers . Recent experiments have demonstrated that plasma processes could be successfully applied to 3D hydrophobic polymer scaffolds, improving the initial cell adhesion and helping cell colonization inside them, in spite of the tortuosity of the porous structures.…”
Section: Introductionmentioning
confidence: 99%
“…It can be observed that the two parameters present a similar trend, as a consequence of the particular geometry of these surfaces. However, as indicated by theory [28], and experimentally demonstrated, RMS has a limited influence on superhydrophobicity: in particular high RMS surfaces exist with poorly hydrophobic characteristics [38]. The r W factor, instead, affects superhydrophobicity since directly correlated to the mean square slope of the surface.…”
Section: Topography Statistical Analysismentioning
confidence: 96%